Initiation into baseball and the preparation of the family to promote its educational function (RIAF. International Journal of Physical Activity, 2023)
The family is considered to be the most important socialization agent, through which students who have become beginners in sports initiation develop their own identities and learn the rules and values of the social environment in which they live. Objective, To socialize the results of the design and implementation of a set of educational actions for the preparation of the families of children who are beginners to baseball in the 7-8 years old category of the municipality of Sancti Spíritus. Materials and Methods: The empirical methods were used: survey, interview, observation, study of documents, analysis group and pre-experiment, combined with other theoretical and mathematical-statistical methods. The sample was made up of fifteen families of children starting baseball in the 7-8 years old category of the Julio Antonio Mella Sports Combine of Sancti Spíritus. Results: The actions implemented achieved a leap in the results of each of the dimensions (cognitive, procedural and attitudinal) with their respective indicators of the preparation of families for their integration into the process of sports initiation in favor of the educational function. Conclusions: It was possible to enhance the preparation of families and with it, a better integration of them to work together with baseball teachers in the sports area, favoring the educational function in this process.
Keywords: Family; Baseball; Sports initiation; Educational Function